Ambient Airborne Particulates of Diameter ⩽1 μm, a Leading Contributor to the Association Between Ambient Airborne Particulates of Diameter ⩽2.5 μm and Children's Blood Pressure. Issue 2 (February 2020) - Wu, Qi-Zhen; Li, Shanshan; Yang, Bo-Yi; Bloom, Michael; Shi, Zhidong; Knibbs, Luke; Dharmage, Shyamali; Leskinen, Ari; Jalaludin, Bin; Jalava, Pasi; Roponen, Marjut; Lin, Shao; et al.
Abstract : Evidence on the associations between airborne particulates of diameter ⩽1 μm (PM1 ) and airborne particulates of diameter ⩽2.5 μm (PM2.5 ) and childhood blood pressure (BP) is scarce. To help to address this literature gap, we conducted a study to explore the associations in Chinese children. Between 2012 and 2013, we recruited 9354 children, aged 5 to 17 years, from 62 schools in 7 northeastern Chinese cities. We measured their BP with a mercury sphygmomanometer. We used a spatiotemporal model to estimate daily ambient PM1 and PM2.5 exposures, which we assigned to participants' home addresses. Associations between particulate matter exposure and BP were evaluated with generalized linear mixed regression models. The findings indicated that exposure to each 10 mg/m 3 greater PM1 was significantly associated with 2.56 mm Hg (95% CI, 1.47–3.65) higher systolic BP and 61% greater odds for hypertension (odds ratio=1.61 [95% CI, 1.18–2.18]). PM1 appears to play an important role in associations reported between PM2.5 exposure and BP, and we found that the ambient PM1 /PM2.5 ratio (range, 0.80–0.96) was associated with BP and with hypertension. Age and body weight modified associations between air pollutants and BP ( P <0.01), with stronger associations among younger (aged ⩽11 years) and overweight/obese children. This study provides the first evidence that long-term exposure to PM1 is associated with hypertension in children, and that PM1 might be a leading contributor to the hypertensive effect of PM2.5 . Researchers and policy makers should pay closer attention to the potential health impacts of PM1 . Abstract : Supplemental Digital Content is available in the text.